Tender frequency and market concentration in balancing power markets - Andreas Knaut; Frank Obermüller; Florian Weiser (Institute of Energy Economics at the University of Cologne (EWI), 2017)
Balancing power markets ensure the short-term balance of supply and demand in electricity markets and their importance may increase with a higher share of fluctuating renewable electricity production. While it is clear that shorter tender frequencies, e.g. daily or hourly, are able to increase the efficiency compared to a weekly procurement, it remains unclear in which respect market concentration will be affected. Against this background, we develop a numerical electricity market model to quantify the possible effects of shorter tender frequencies on costs and market concentration. We find that shorter time spans of procurement are able to lower the costs by up to 15%. While market concentration decreases in many markets, we - surprisingly - identify cases in which shorter time spans lead to higher concentration.
Keywords: D47; L94; 330; Balancing Power; Market Design; Market Concentration; Tender Frequency; Provision Duration; Mixed Integer Programming